Perceived Parenting Styles and Parental Inconsistency Scale: Construct Validity in Young Adults - de la Iglesia, Guadalupe (2014)
The study examinesevidences of construct validity of the Perceived Parental Styles and Parental Inconsistency scale –EPIPP–, on a sample of 369 young adults. Individuals were asked about their father and their mother by means of 24 items. These conformsix subscales that constitutea first-order-model–Affection, Dialogue, Indifference, Verbal Coercion, Physical Coercion and Prohibition–that additionally group into two major scales –a second-order model–:Responsiveness and Demandingness.A confirmatory factor analysis was carried out on the first-orderand second-order factor structures,using maximum likelihood anda bootstrap procedure with 500 random samples. Resulting indexes showed an excellent fit in both modelsfor theFatherand Motherversions. Furthermore, adequate resultswere obtained in a cross-validation and afactorial invariance analysis. This way, solid evidences of construct validity were obtained for the EPIPP, suggesting it for the assessmentof perceived parenting in young adults.